Perbandingan Kadar Kortisol dan Efek Analgesia Pascabedah Anestesi Spinal Kombinasi Bupivakain Hiperbarik 0,5% 8 mg dan Klonidin 30 μg dengan Bupivakain Hiperbarik 0,5% 8 mg dan Morfin 0,1 mg pada Pasien yang Menjalani Prosedur Seksio Sesaria - Irawan, Hery; , Wahyudi; , Hisbullah (Majalah Anestesia dan Critical Care, 2014)
Penurunan hormon kortisol pada masa intraoperatif dapat terjadi dengan menggunakan mekanisme penghambatan pada sistem saraf pusat. Anestesi spinal merupakan pilihan dalam mekanisme tersebut. Penelitian bertujuan untuk membandingkan kadar kortisol dan efek analgesia pascabedah pada anestesi spinal kombinasi Bupivakain hiperbarik 0,5% 8 mg+Klonidin 30 μg dan Bupivakain hiperbarik 0,5% 8 mg + morfin 0,1 mg pada seksio sesarea. Penelitian menggunakan uji klinis acak tersamar tunggal pada 50 pasien dengan kriteria inklusi, dibagi menjadi kelompok anestesi spinal kombinasi Bupivakain hiperbarik 0,5% 8 mg + Klonidin 30 μg (BK) n=25 dan kelompok kombinasi Bupivakain hiperbarik 0,5% 8 mg + morfin 0,1 mg (BM) n=25. Analisis statistik dengan Uji Mann-whitney dan uji-tes, dengan p<0,05 bermakna secara signifikan. Hasil penelitian menunjukkan pada kelompok BM sama efektif dengan kelompok BK dalam mencegah peningkatan kadar kortisol intraoperatif. Efek analgesia pascabedah anestesi spinal kombinasi kelompok BM lebih baik dibandingkan dengan kombinasi BK. Efek samping diantara kedua kelompok dinyatakan tidak bermakna. Kesimpulan penelitian adalah kelompok BM sama efektif dengan kelompok BK dalam mencegah peningkatan kadar kortisol saat pembedahann namun e fek analgesia pascabedah anestesi spinal kombinasi kelompok BM lebih baik dibandingkan dengan kombinasi BK. Kata kunci: Anestesi spinal, kortisol, klonidin, morfin, seksio sesarea The decrease of cortisol hormone level during intraoperative period may occur due to inhibitory mechanism on central nervous system. Spinal anesthesia is an option to prevent the proccess. This study aimed to compare cortisol hormone level and postoperative analgesia between spinal anesthesia combination of 0.5% hyperbaric Bupivacaine 8 mg and Clonidine 30 μg + hyperbaric 0.5 % Bupivacaine 8 mg + 0.1 mg morphine in cesarean section. The study was a single-blind randomized clinical trial in 50 patients with inclusion criteria, divided into BK group (a combination of 0.5 % Hyperbaric Bupivacaine 8 mg + 30 mg Clonidine; n=25) and BM group (a combination of 0.5 % hyperbaric Bupivacaine 8 mg + morphine 0.1 mg; n=25). Statistically analyzed using Mann-Whitney Test and t-test, with p<0.05 statistically significance. Research shows that BM group as effective as BK group in preventing the increase of cortisol level. Effect of postoperative analgesia in group BM was better than group BK. Side effects between the two groups revealed no significant difference. The conclusion of this study group BM as effective as group BK in preventing the increase of cortisol level during surgery. However, effect of postoperative analgesia in group BM was better than group BK.Key words: Cortisol, caesarean section, clonidin, morphin, spinal anesthesia. Reference Hurley RW, Wu CL. Acute post operative pain. dalam: Miller RD, Eriksson LI, Fleisher LA, Wiener JP, Young WL, penyunting. Miller’s anesthesia. Edisi ke-7. Philadelphia: Elsevier Churchill Livingstone; 2008. hlm. 321–33. Paech MJ. Anesthesia for cesarean delivery. Dalam: Palmer CM, D’Angelo R, Paech MJ, penyunting. Obstetric anesthesia. New York: Oxford University Press; 2011. hlm.79–155. Ahmad MR, Marwoto. Pengelolaan nyeri pasca seksio sesaria. Dalam: Bisri T, Wahjoeningsih S, Suryono B, penyunting. Anestesi Obstetri. Bandung: Saga Olahcitra; 2013. hlm. 301–12. Persec J, Persec Z, Zinovic H. Post operative pain and systemic inflammatory stress response after preoperative analgesia with clonidine or levobupivacaine: a randomized controlled trial. Br J Anesth. 2009;121(17–18):558–3. Bhure A, Kalita N, Ingley D, Gadkari CP. Comparative study of intrathecal hyperbaric Bupivakaine with clonidine, fentanyl and midazolam for quality of anaesthesia and duration of post operative pain relief in patients undergoing elective caesarean section. People J of Sci Research. 2012; 5(1):19–23. Bhushan SB, Suresh JS, Vinayak SR, Lakhe JN. Comparison of different doses of clonidine as an adjuvant to intrathecal Bupivakaine for spinal anesthesia and postoperative analgesia in patients undergoing caesarian section. Anaesth, Pain Intens Care. 2012;16(3):266– 72. Pongpit P. Comparison postoperative analgesic efficacy of intrathecal morphine and without intrathecal morphine in patients who underwent cesarean section with spinal anesthesia in Nakhonphanom hospital: a rectrospective observational analitycal study. Yasothon Med Jr. 2014;14(2):1–3. Rochette A, Raux O, Troncin R, Dadure C, Verdier R, Capdevila X. Clonidine prolongs spinal anesthesia in newborns: a prospective dose-ranging study. Anesth Analg. 2004;98: 56–9. Kwan JW. Use of infusion devices for epidural or intrathecal administration of spinal opioids. Am J Hosp Pharm 2008;47:18–23. Tanra, AH. Nyeri pascabedah implikasi sensitisasi perifer dan sentral. Dalam: makalah simposium pengelolaan nyeri. Jakarta. 2004. Prasetyo AH. Efek klonidin sebagai ajuvan anestesi spinal terhadap hormon stress [Tesis]. Surakarta; 2011. Cianni S, Rossi M, Casta A. Spinal anesthesia: an evergreen technique. Acta Biomed. 2008; 79:9–17. Vercauteren M. Analgesia after Caesarean section: are neuraxial techniques outdated?. Jr Român de Anestezie Terapie Intensivã 2009;16(2):129–133. Kirsten M, Laura M. Bohn. Mu opiod receptor regulation and opiate responsiveness. The AAPS Journal. 2005;7(3):572–83. Tonner PH. Alpha2- adrenoceptor agonis in anaesthesia. Europ Anesth society. 2004; 35–40. Vercauteren M. Analgesia after Caesarean delivery in the 21st century. ESA Jr.2009 ;(13):1–2 Zhou H, Chen SR, Chen H, Pan HL. Opioidinduced long-term potentiation in the spinal cord is a pre synaptic event. J Neuro Sci. 2010; 30(12):4460–6. Miller RD, penyunting.Bupivakaine. Edisi ke-6. New York: Elsevier, Churchill Livingstone; 2006. Gadsden J, Hart S, Santos AC. Post-cesarean delivery analgesia. Anesth Analg. 2005; 101:62–9. Christiansson L. Update on adjuvant in regional anesthesia. Period boil. 2009; 111(2): 161–70.